URINE ALBUMIN EXCRETION IN NON-DIABETIC NORMOTENSIVE HEALTHY ADULTS WITH NORMAL RENAL FUNCTION - R, Aarthi; Prakash vr, (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives:The aim of our study is to measure the urine albumin excretion in apparently healthy adults, to find out the prevalence of elevated urine albumin excretion and to correlate urine albumin excretion with anthropometric parameters. Methods: For this, Cross sectional study was conducted where healthy adults of age group 35-50 years were taken. Systolic, diastolic blood pressures, fasting plasma glucose, 2hr post prandial glucose, serum urea, serum creatinine, serum cholesterol, serum HDL cholesterol, serum LDL cholesterol, estimated creatinine clearance, body mass index, body surface area, mid arm circumference, waist circumference, hip circumference, wasit:hip ratio, mid thigh circumference, mid calf circumference, urine albumin, urine creatinine, urine albumin creatinine ratio were measured. The relationship between urine albumin creatinine ratio and the individual anthropometric measures were studied using spearman rank correlation analysis. Results: Two out of fifty four participants had a urine albumin creatinine ratio in excess of 30microg/mg which signifies microalbuminuria. This corresponds to a prevalence of 3.7%.Urine albumin creatinine ratio correlated positively with the waist circumference and waist hip ratio. The relationship with other anthropometric measures were negative. None of them found to be significant.